2014
DOI: 10.1109/ted.2014.2356597
|View full text |Cite
|
Sign up to set email alerts
|

Improved Interfacial and Electrical Properties of Ge-Based Metal-Oxide-Semiconductor Capacitor With LaTaON Passivation Layer

Abstract: The interfacial and electrical properties of Ge-based metal-oxide-semiconductor (MOS) capacitor with high-k gate dielectric of HfTiO and passivation interlayer of LaTaON are investigated. Experimental results show the Ge MOS with HfTiO/LaTaON gate-stacked dielectric exhibits low interfacestate density (7.8 × 10 11 cm −2 eV −1 ), small gate-leakage current (7.88 × 10 −4 A cm −2 at V g − V fb = 1 V), small capacitance equivalent thickness (1.1 nm), and large equivalent dielectric constant (27.7). X-ray photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The obvious peak at 1220.10 eV is in good agreement with the banding energy of 1220.2-1220.6 eV for GeO 2 . [9] Also, the peak at 33.20 eV is in accordance with the banding energy of GeO 2 [14] as shown in Fig. 3(a), which matches with 32.3-33.6 eV of GeO 2 .…”
Section: Binding Energy (Ev)supporting
confidence: 68%
See 1 more Smart Citation
“…The obvious peak at 1220.10 eV is in good agreement with the banding energy of 1220.2-1220.6 eV for GeO 2 . [9] Also, the peak at 33.20 eV is in accordance with the banding energy of GeO 2 [14] as shown in Fig. 3(a), which matches with 32.3-33.6 eV of GeO 2 .…”
Section: Binding Energy (Ev)supporting
confidence: 68%
“…[4,7] However, because of its hygroscopic nature, La-based oxides seem unsuitable for being directly used as gate dielectric or passivation interlayer. [8] For solving the problem, Ji et al [9] prepared a LaTaON dielectric used as a passivation interlayer by doping Ta into La-based oxides in N 2 atmosphere, achieving a good interfacial quality and electrical characteristics. Further, Cheng et al [10] reported that incorporation of Ta into LaON can improve its hygroscopic nature, and directly used LaTaON as the high-𝑘 gate dielectric of Ge MOS and obtained good results.…”
mentioning
confidence: 99%
“…The energy scale of the three samples is calibrated by fixing the Ge 3d peak of the Ge substrate at a binding energy (BE) of 28.8 eV to eliminate the charging effect on the samples. Because of a strong overlap between the Ge 3d peak and Hf or Ta peak, 4,24 the Ge 2p 3/2 core level spectrum of the samples is used, as shown in Fig. 4.…”
Section: Function Difference Between the Al Gate Andmentioning
confidence: 99%
“…3) Therefore, suppressing the growth of the suboxides on the surface of Ge as well as obtaining a highquality interface between high-k gate dielectric and Ge substrate have become critical events to fabricate Ge-based MOSFETs. For this purpose, various surface passivation layers such as AlON, 4,5) LaTaON 6) and so on have been investigated to obtain good interface quality with Ge. Reasonable passivation of Ge MOS interface can suppress coulomb scattering and enhance carrier mobility.…”
mentioning
confidence: 99%